Glutathione‐stabilized Cu nanocluster‐based fluorescent probe for sensitive and selective detection of Hg2+ in water. (18th April 2017) - Luo, Tingting; Zhang, Shiting; Wang, Yujue; Wang, Meina; Liao, Mei; Kou, Xingming
Abstract: In this paper, an innovative and facile one‐pot method for synthesizing water‐soluble and stable fluorescent Cu nanoclusters (CuNCs), in which glutathione (GSH) served as protecting ligand and ascorbic acid (AA) as reducing agent was reported. The resultant CuNCs emitted blue‐green fluorescence at 440 nm, with a quantum yield (QD) of about 3.08%. In addition, the prepared CuNCs exhibited excellent properties such as good water solubility, photostability and high stability toward high ionic strength. On the basis of the selective quenching of Hg 2+ on CuNCs fluorescence, which may be the result of Hg 2+ ion‐induced aggregation of the CuNCs, the CuNCs was used for the selective and sensitive determination of Hg 2+ in aqueous solution. The proposed analytical strategy permitted detection of Hg 2+ in a linear range of 4 × 10 −8 to 6 × 10 −5  M, with a detection limit of 2.2 × 10 −8  M. Eventually, the practicability of this sensing approach was confirmed by its successful application to assay Hg 2+ in tap water, Lotus lake water and river water samples with the quantitative spike recoveries ranging from 96.9% to 105.4%.